HETEROSIS STUDIES FOR YIELD AND YIELD CONTRIBUTING TRAITS IN BREAD WHEAT (TRITICUM AESTIVUM L.) - DEVI, E. LAMALAKSHMI; SWATI; GOEL, PRASHANT; SINGH, MAMTA; J.P. JAISWAL (The Bioscan, 2013)
A study was conducted in bread wheat to estimate the magnitude of heterosis for grain yield and its seven yield components. 36 F1 hybrids were derived from crosses between twelve female lines and three testers using line x tester analysis and these F1s along with 15 parents and 2 commercial check varieties were evaluated during Rabi 2010-11 using Randomized Block Design. Highly significant differences were observed among the genotypes for all the traits studied. The cross UP 2596 X DBW 17 was recognized as the best heterotic cross for grain yield as it exhibited highly significant positive heterosis over both the standard checks UP 2554 and PBW 343. The cross HW 2019 x UP 2338 exhibited highest and significant positive heterosis over better parent, mid parent and over both the standard checks for number of grains per spike. The present study reveals good scope for isolation of pure lines from the progenies of heterotic F1s as well as commercial exploitation of heterosis in bread wheat.